2013
DOI: 10.6106/jcepm.2013.3.3.042
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Safety and Quality Issues in the Construction Industry

Abstract: Construction industry is considered as the most hazardous industry due to its unique nature. Safety and quality management are essential to control hazards and improve success in project implementation. This paper focuses on evaluating the crucial factors influencing safety and quality management in construction projects. In order to achieve this, the qualitative and quantitative approaches were used for data collection. The findings of this study reveal the crucial safety factors as management commitment, saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…According to ranking proposed by Ogwueleka [7] quality factors are ranked as follows: employee involvement, expertise knowledge, focus on customer/customer satisfaction, communication, which differs from the ranking factors obtained in the scope of this research.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to ranking proposed by Ogwueleka [7] quality factors are ranked as follows: employee involvement, expertise knowledge, focus on customer/customer satisfaction, communication, which differs from the ranking factors obtained in the scope of this research.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In this research, project management is observed as a process and, at the end of each phase, the project delivers products (i.e. product quality factors) [4,5,7,22,23]. Factors presented in Table 2 have been identified as factors of the process (project management process) and product (deliverables), which were selected and amended (after analysis and consultation with university professors).…”
Section: Quality and Key Quality Factors Of The Project Management Prmentioning
confidence: 99%
See 2 more Smart Citations
“…If quality is managed in a proper manner, it can improve the project success rate and organizational viability (Ogwueleka 2013).…”
Section: Introductionmentioning
confidence: 99%